Urban Architecture in Malabero Village, The Old City of Bengkulu - Dwi Rina Utami; Djoko Wijono (Built Environment Studies, 2020)
Urban architecture in Malabero village is an interesting part to be researched. This is demonstrated by several elements of urban architecture that illustrate specific characteristics such as the Thomas Parr Monument, the Old Post Office, Merdeka Square, Kampung Cina, Bengkulu Malay settlement, a settlement built on the coastline and various building build on the sea embankment. This research was conducted to determine the configuration of contemporary architecture in Malabero and how it happen using qualitative and explorative methods. The research results that architecture configuration of the street in Malabero village consists of spread and linear organic patterns. Architecture configuration of building and space on the settlement scale based on ethnicity with diverse characteristics and tend to follow the street with linear patterns, meanwhile on the urban scale tend to the octopus shape cities. The configuration of infrastructure and vegetation in Kampung Cina and Merdeka Square is complete and well designed. Furthermore, the configuration of signages tend to be found at the cross street. This research also revealed that the architecture configuration was formed due to several factors such as historical, geographical, policy, and control of the government, economic, socio-cultural, important event, and lifestyle.